First-principles atomic level stresses: application to a metallic glass under shear - Ivan Lobzenko; Tomohito Tsuru; Yoshinori Shiihara; Takuya Iwashita (Materials Research Express, 2023)
Unlike crystalline alloys, metallic glasses (MGs) do not possess distinctive defects but exhibit a highly heterogeneous response to shear deformation. The difficulties in describing such non-uniform behaviour hamper the prediction of the mechanical properties of MGs. Using the first-principles athermal quasi-static shear simulation on a CuZr glass, we investigate the mechanical responses of various atomic-level parameters, such as the first-principles atomic stresses and electronic properties (an atomic charge, chemical bonds, etc), and their correlations. We find that the atomic von Mises stress is correlated with a ${D}_{\min }^{2}$ parameter, which is commonly employed and also serves as a unique measure of the degree of non-uniform responses. We also show little correlation between the mechanical and electronic properties during the relaxation process, while we perceive a high correlation between the change in chemical and topological bonds. We discuss the physical insights behind these correlations.